Application of Activity Based Costing Method in Cost Calculation - Istanti, Enny; Rachmansyah, Moch. Rizaldy; Firmansyah, Moch. Rachmandany; GS, Achmad Daengs (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to analyze the implementation of the Activity Based Costing (ABC) method in cost calculation for service units at the Orthopedic & Traumatology Hospital in Surabaya and to compare the results with the conventional costing method currently used by the hospital. Design/methodology/approach: The studies employ a descriptive-comparative method with a quantitative and qualitative approach. The data used include the hospital’s financial reports, particularly unit-level income statements, as well as information from interviews regarding activities and costs within each service unit. Data analysis was carried out in three stages: documenting costs, identifying activities and cost drivers, and calculating costs using the ABC method. Findings: The results show that the ABC method provides more accurate and relevant cost calculations because it is based on the actual activities performed in each unit. Cost calculations using ABC also yield more reasonable unit-level profit and loss results compared to the conventional method, which still allocates costs based on revenue percentages. These findings indicate that applying the ABC method can assist hospital management in determining fairer, more transparent service rates that reflect the resource consumption of each unit. Paper type: Research paper.